Incidence of Severe Hepatotoxicity Related to Antiretroviral Therapy in HIV/HCV Coinfected Patients - Emily L. Heil; Mary L. Townsend; Kenneth Shipp; Amy Clarke; Melissa D. Johnson (AIDS Research and Treatment)
Introduction. Hepatotoxicity is a concern in HIV/hepatitis C virus (HCV) coinfected patients due to their underlying liver disease. This study assessed the incidence of hepatotoxicity in HIV/HCV co-infected patients in two outpatient infectious diseases clinics. Methods. HIV/HCV co-infected adults were included in this retrospective study if they were PI or NNRTI naïve at their first clinic visit and were initiated on an NNRTI- and/or PI-based antiretroviral regimen. Patients were excluded if they had active or chronic hepatitis B virus (HBV). The primary objective was to determine the overall incidence of severe hepatotoxicity. Results. Fifty-six of the 544 patients identified met inclusion criteria. The incidence of severe hepatotoxicity was 10.7% (6/56 patients). Severe hepatotoxicity occurred with efavirenz (𝑁=2), nevirapine (𝑁=1), indinavir (𝑁=1), nelfinavir (𝑁=1), and saquinavir/ritonavir (𝑁=1). Conclusion. The incidence of severe hepatotoxicity appears to be low in this retrospective analysis of HIV/HCV co-infected patients receiving a PI-and/or NNRTI-based regimen.